Pengaruh Pelatihan, Kepemimpinan, dan Motivasi terhadap Kinerja Karyawan pada PD BPR Bank Jogja Yogyakarta - Nur Hayati; Sri Haryani (Telaah Bisnis, 2017)
The purpose of this study is to analyze the effect of training (X1), leadership (X2), and motivation (X3) on dependent variable employee performance (Y). The population in this study are operational staff in PD BPR Bank Jogja in Yogyakarta. Most of the operational staff of PD BPR Bank Jogja is female and their ages range from 21 to 50 years. Lowest Education of operational staff is Diploma and some of them are Magister (S2). This company is growing as indicated by the increase in the number of staff from time to time. Determination of the number of samples using methods Slovin, samples taken 80. The sampling method using a non-probability sampling with purposive sampling method, the sampling technique is based on the consideration that in accordance with the purpose of research. Collecting data using questionnaires distributed to 80 respondents. The results of multicollinearity, heteroscedasticity, and autocorrelation classical assumption test show that there is no multicollinearity problems among the independent variables, there is no heteroscedasticity in regression models, and there is no autocorrelation. Data were analyzed using multiple linear regression. The results show that the training and motivation have a positive effect on performance, while the leadership has a negative effect on performance. T test results showed that the only variable motivation partially influence on performance, training and leadership variables were partially no effect on employee performance. The F test results showed that the variables of training, leadership, and motivation simultaneously affect the performance of employees.